Supplier-Supplier Relationships in Buyer-Supplier-Supplier Triads: Implications for Supplier Performance - Wu,Zhaohui; Choi,T.Y.; Rungtusanatham,M. (Journal of Operations Management, 2010)
A growing number of studies and evidence from industries suggest that, besides managing the relationship with its suppliers, a buyer needs to proactively manage the relationships between those suppliers. In a buyer–supplier–supplier relationship triad, the buyer, as the contracting entity, influences the suppliers’ behaviors and the relationship between them. By considering the relationships in such a triad, we are able to gain a richer and more realistic perspective of buyer–supplier relationships. In this study, our goal is to examine supplier–supplier relationships in buyer–supplier–supplier triads, focusing on how such relationships impact the supplier performance. We frame the supplier–supplier relationship as co-opetition—one in which competing suppliers work together to meet the buyer's requirements. We investigate the role of the buyer on such relationships, and how the buyer and co-opetitive supplier–supplier relationships affect supplier performance. We find mixed empirical support for our hypotheses. However, we are able to demonstrate the dynamics of supplier–supplier co-opetition in the buyer–supplier–supplier triad. We point out the need for further studies in this area.
Keywords: Supply Chain